Nanomechanics of bidentate thiolate ligands on gold surfaces - Zoloff Michoff, Martin Eduardo (2015)
The effect of the chain length separating sulfur atoms in bidentate thiols attached to defective gold surfaces on the rupture of the respective molecule-gold junctions has been studied computationally. Thermal desorption always yields cyclic disulfides. In contrast, mechanochemical desorption leads to cyclic gold complexes, where metal atoms are extracted from the surface and kept in tweezer-like arrangements by the sulfur atoms. This phenomenon is rationalized in terms of directional mechanical manipulation of Au-Au bonds and Au-S coordination numbers. Moreover, the flexibility of the chain is shown to crucially impact on the mechanical strength of the junction.